Experimental Investigation on the Micro Structural and Flame Retardant Properties of Various Natural Fiber Reinforced Composites - Deepak Sampathkumar; Ashokkumar Mohankumar; Arul Kulandaivel; Vignesh Packkirisamy (Journal of Natural Fibers)
The objective of this work is to examine the fire resistance of natural composite materials (NCM). The reinforcements used in this work are coir, cotton, Palmyra leaf stream, sisal fiber, and matrix selected for natural rubber resin (latex). The fibers as reinforcement and natural rubber as the matrix phase were considered, and then the composite was manufactured through the hand lay-up open mold method. The chemical compositions of specimens treated with inorganic flame retardant chemicals (Al(OH)3, Mg(OH)2, zinc borate, ZnO, and zirconium oxide). The selection of flame retardant chemicals is based on their high melting temperature, low toxicity, low smoke emission, low burning rate, easy availability, and low cost. The thermal analysis of the horizontal burn test, TGA, DSC, and cone calorimeter analysis was carried out to understand the material’s thermal stability. The important finding of this experimental work is to analyze the micro structural and thermal stability of various compositions of flame-retardant composite materials. In all aspects, the zinc-borate and zirconium oxide-added composites show more advantages in flame retardant properties compared to other composite materials.